Complement activating antibodies to myelin oligodendrocyte glycoprotein in neuromyelitis optica and related disorders - Mader, Simone; Gredler, Viktoria; Schanda, Kathrin; Rostasy, Kevin; Dujmovic, Irena; Pfaller, Kristian; Lutterotti, Andreas; Jarius, Sven; Pauli, Franziska di; Kuenz, Bettina; Ehling, Rainer; Hegen, Harald; et al. (Journal of neuroinflammation, 2011)
Serum autoantibodies against the water channel aquaporin-4 (AQP4) are important diagnostic biomarkers and pathogenic factors for neuromyelitis optica (NMO). However, AQP4-IgG are absent in 5-40% of all NMO patients and the target of the autoimmune response in these patients is unknown. Since recent studies indicate that autoimmune responses to myelin oligodendrocyte glycoprotein (MOG) can induce an NMO-like disease in experimental animal models, we speculate that MOG might be an autoantigen in AQP4-IgG seronegative NMO. Although high-titer autoantibodies to human native MOG were mainly detected in a subgroup of pediatric acute disseminated encephalomyelitis (ADEM) and multiple sclerosis (MS) patients, their role in NMO and High-risk NMO (HR-NMO; recurrent optic neuritis-rON or longitudinally extensive transverse myelitis-LETM) remains unresolved.
Gesehen am 25.11.2022